A comparative study of the acceptance and understanding of evolution between China and the US. (January 2022) - Zhang, Mingjun; Weisberg, Deena Skolnick; Zhu, Jing; Weisberg, Michael
Prior work has found that Americans' views on evolution are significantly and positively related to their understanding of this theory. However, whether this relationship is cross-culturally robust is unknown. This article extends earlier work by measuring and comparing the acceptance and understanding of evolution among highly educated individuals in China and the United States. We find a significantly higher evolution acceptance level in the Chinese sample than in the US sample, but no significant difference in their average levels of evolution knowledge. Our analysis also shows that accepting evolutionary theory is related to understanding in both the US and the Chinese samples. These results provide evidence for the robustness of the relationship between understanding and acceptance of evolution across different cultural contexts. To our knowledge, this is the first attempt to comprehensively test understanding of evolutionary theory within a Chinese sample and to compare these results with the US sample.